Correlation of Serum Vitamin D Levels with the Severity of Diabetic Foot Ulcers in Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Vidro Alif Gunawan; Kemas Muhammad Dahlan; Legiran (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2023)
Background: Vitamin D has a role in diabetes mellitus. Low levels of vitamin D are associated with the development of diabetic foot infections. Effects of vitamin D supplementation on wound healing, insulin resistance, inflammatory biomarkers, and oxidative stress are mediated by effects on induction of phagocytosis and bacterial killing by macrophages, suppression of interferon-gamma mediating macrophage activation, activation of insulin receptor expression, and downregulation from cytokines. This study aimed to determine the correlation between serum vitamin D levels and the severity of diabetic foot ulcers in Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: This study was an observational analytics study, where as many as 30 research subjects participated in this study. The study observed vitamin D levels and the severity of diabetic foot ulcers as assessed by the classification of the wound, ischemia, and foot infection (WIfI). Univariate and bivariate data analysis was carried out using SPSS. Results: The results of Sommer's correlation statistical test obtained a value of p = 0.001 (p <0.05) with a correlation strength of r = 0.564, which means sufficient strength (r = 0.40-0.70). This means that the higher the deficiency in serum Vitamin D levels, the higher the degree of WIfI classification experienced. Conclusion: There is a correlation between serum vitamin D levels and the severity of diabetic foot ulcers in Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia.